Live to Work or Love to Work: Work Craving and Work Engagement - Wojdylo, Kamila; Baumann, Nicola; Fischbach, Lis; Engeser, Stefan (PLOS ONE, 2014)
Objective According to the theory of work craving, a workaholic has a craving for self-worth compensatory incentives and an expectation of relief from negative affect experienced through neurotic perfectionism and an obsessive-compulsive style of working. Research has shown that workaholism and work engagement should be considered as two distinct work styles with different health consequences. However, the mechanisms underlying the adoption of these work styles have been neglected. The present study proposes that work craving and work engagement are differentially associated with self-regulatory competencies and health. In particular, we expected that the working styles mediate the relationships between emotional self-regulation and health. Methods: In the cross-sectional study, 469 teachers from German schools completed online administered questionnaires. By means of structural equation modeling, we tested two indirect paths: a) from self-relaxation deficits via work craving to poor health and b) from self-motivation competencies via work engagement to good health. Results As expected, we found evidence that a) the negative relationship of self-relaxation deficits on health was partially mediated by work craving and b) the positive relationship of self-motivation competencies on health was partially mediated by work engagement. Conclusions The present study emphasizes the importance of self-regulation competencies for healthy or unhealthy work styles. Whereas work craving was associated with a low ability to down-regulate negative emotions and poor health, work engagement was associated with a high ability to up-regulate positive emotions and good health.